Osteoarthritis-related nociceptive behaviour following mechanical joint loading correlates with cartilage damage. Issue 3 (March 2020) - ter Heegde, F.; Luiz, A.P.; Santana-Varela, S.; Magnúsdóttir, R.; Hopkinson, M.; Chang, Y.; Poulet, B.; Fowkes, R.C.; Wood, J.N.; Chenu, C.
Summary: Objective: In osteoarthritis (OA), the pain-structure relationship remains complex and poorly understood. Here, we used the mechanical joint loading (MJL) model of OA to investigate both knee pathology and nociceptive behaviour. Design: MJL was used to induce OA in the right knees of 12-week-old male C57BL/6 mice (40 cycles, 9N, 3x/week for 2 weeks). Mechanical sensitivity thresholds and weight-bearing ratios were measured before loading and at weeks one, three and six post-loading. At these time points, separate groups of loaded and non-loaded mice ( n = 12/group) were sacrificed, joints collected, and fur corticosterone levels measured. μCT analyses of subchondral bone integrity was performed before joint sections were prepared for nerve quantification, cartilage or synovium grading (scoring system from 0 to 6). Results: Loaded mice showed increased mechanical hypersensitivity paired with altered weight-bearing. Initial ipsilateral cartilage lesions 1-week post-loading (1.8 ± 0.4) had worsened at weeks three (3.0 ± 0.6, CI = −1.8–0.6) and six (2.8 ± 0.4, CI = −1.6–0.4). This increase in lesion severity correlated with mechanical hypersensitivity development (correlation; 0.729, P = 0.0071). Loaded mice displayed increased synovitis (3.6 ± 0.5) compared to non-loaded mice (1.5 ± 0.5, CI = −2.2–0.3) 1-week post-loading which returned to normal by weeks three and six. Similarly, corticosterone levels were only increased at week one post-loading (0.21 ± 0.04 ng/mg) compared to non-loaded controls (0.14 ± 0.01 ng/mg, CI = −1.8–0.1). Subchondral bone integrity and nerve volume remained unchanged. Conclusions: Our data indicates that although the loading induces an initial stress reaction and local inflammation, these processes are not directly responsible for the nociceptive phenotype observed. Instead, MJL-induced allodynia is mainly associated with OA-like progression of cartilage lesions.